Length of resin tags in pit-and-fissure sealants: all-in-one self-etching adhesive vs phosphoric acid etching. - dos Santos, Karina Tonini; Sundfeld, Renato Herman [UNESP]; Garbin, Clea Adas Saliba [UNESP]; de Alexandre, Rodrigo Sversut; Sundefeld, Maria Lúcia Marçal Mazza [UNESP]; Ceolim, Bruna Nakae (My University, 2008)
PURPOSE: To investigate the penetration (tags) of adhesive materials into enamel etched with phosphoric acid or treated with a self-etching adhesive, before application of a pit-and-fissure sealant. MATERIALS AND METHODS: The sample comprised six study groups with six specimens each. Before pit-and-fissure sealing with the materials Clinpro SealantTM (Groups I and II), Vitro Seal ALPHA (Groups III and IV) and Fuji II LC (Groups V and VI), the teeth in Groups I, III, and V were etched with 35% phosphoric acid for 30 seconds. Teeth in Groups II, IV, and VI received application of the self-etching adhesive Adper Prompt L-Pop. The treated teeth were sectioned buccolingually, ground to 100-microm thickness, decalcified, and analyzed by conventional light microscopy at 400x magnification. RESULTS: The teeth etched with phosphoric acid exhibited significantly greater penetration than specimens treated with self-etching adhesive. CLINICAL SIGNIFICANCE: When compared with enamel treated with a self-etching adhesive, the penetration (tags) of adhesive materials into enamel was greater when applied on enamel etched with phosphoric acid.
Keywords: biomedical and dental materials; Clinpro Sealant; compomer; dentin bonding agent; fissure sealant; Fuji glass ionomer lining cement; Fuji glass-ionomer lining cement; glass ionomer; phosphoric acid; Prompt L Pop; Prompt L-Pop; resin; resin cement; chemistry; comparative study; dental acid etching; dental bonding; enamel; human; materials testing; methodology; surface property; ultrastructure; Acid Etching, Dental; Compomers; Composite Resins; Dental Bonding; Dental Enamel; Dental Materials; Dentin-Bonding Agents; Glass Ionomer Cements; Humans; Materials Testing; Phosphoric Acids; Pit and Fissure Sealants; Resin Cements; Surface Properties